Cultural Capital, Educational Attainment, and Economic Opportunity among First-Generation Migrants in Jakarta - Prahitaningtyas, Sherina (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
Migration to Jakarta has created new opportunities as well as barriers for first-generation migrants seeking to translate their educational background into sustainable employment. Despite relatively high levels of schooling among migrants, a large share remains concentrated in informal work, suggesting that factors beyond formal education shape labor-market outcomes. This study examines the role of cultural capital—specifically language proficiency, credential recognition, and community engagement—in influencing educational attainment and economic opportunity among first-generation migrants in Jakarta. Using a quantitative explanatory research design, data were collected from 400 respondents selected through stratified random sampling. A structured questionnaire was validated through Confirmatory Factor Analysis and reliability was confirmed with Cronbach’s Alpha. Data were analyzed using SPSS 27 and AMOS 24, employing multiple regression and structural equation modeling. The findings reveal that cultural capital significantly predicts educational attainment, which in turn mediates access to formal employment and higher earnings. Language proficiency emerged as the strongest predictor, while challenges in recognizing provincial educational credentials contributed to underemployment. The results confirm theoretical perspectives from Bourdieu on cultural capital and Piore on segmented labor markets, emphasizing how structural and cultural factors intersect to shape migrant trajectories. The study implies that policies to enhance credential recognition, language training, and inclusive labor practices are essential for fostering migrant integration and reducing inequality. These insights contribute to both theoretical debates and practical strategies for managing migration in rapidly urbanizing contexts.